It's this war - R. Finlayson (Law Text Culture, 1998)
it's this war that's raging off on the horizon my heart the war that's singing missiles of love across the wire the war that's wandering into my kitchen into the bath the news of the world the songs of the dead friends the great hope oflaughter as I step up into the light on the red red plain and wonder at the beauty ofspinifex off to the sky